13q Deletions detected by fluorescence in situ hybridization for diagnosis and prognosis of chronic lymphoproliferative neoplasms - Sitko, V.V.; Misharina, J.A.; Minchenko, J.M.; Poluben, L.O.; Dmitrenko, O.O.; Silaiev, Y.O.; Kostyukova, N.I.; Tkachenko, O.V.; Tovstogan, A.O.; Polyanska, V.M.; Lyashenko, L.O.; Bebeshko, V.G. (Вiopolymers and Cell, 2015)
Aim. Determination of deletion of the long arm of chromosome 13 in the patients with chronic lymphocytic leukemia, diffuse large B-cell lymphoma and multiple myeloma to provide prognostic assessments of Chronic Lymphoproliferative Neoplasms (CLPN) sub-variants progression, and early detection of therapy resistant cases and relapses of CLPN. Methods. Preparations of bone marrow cells from all patients (n = 115) with CLPN were studied. Fluorescence in situ hybridization was performed using commercial test Vysis LSI D13S319 (13q14.3) Spectrum Orange/ Vysis LSI 13q34 Spectrum Green FISH probe kit (Abbott Molecular, USA). Results. The molecular cytogenetic investigations have revealed deletions of 13q in 38 % of the patients with CLPN. We also present a clinical case where the deletion of 13q is detected along with other cytogenetic aberrations that significantly impair a disease prognosis. Conclusion. The analysis of deletions of the long arm of chromosome 13 is an important diagnostic and prognostic criterion, which assists to optimizes the treatment of the patients with CLPN.